2021
DOI: 10.34071/jmp.2021.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression and the Associated Factors Among the Elderly in Some Communities of Thua Thien Hue Province

Abstract: Introduction: Currently, Vietnam is entering the aging population stage and is one of the fastest aging countries worldwide. Old age increases the risk of chronic diseases, particularly mental health disorders. Objective: investigated the prevalence of depression and examined the associated factors with depression among older people. Methods: A cross-sectional study was implemented in 760 older people in some communities of Thua Thien Hue province from January to August 2020. Data were collected by directinter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Table 2 shows the depression rate of medical and pharmacy students in a number of Vietnamese studies, showing that the depression rate of students is increasing, and this rate is quite consistent with quantitative studies, previously, most domestic and foreign studies showed that the rate of students suffering from depression was very high during their school years [12][13][14]. This is explained by the large amount of knowledge, dense class schedule as well as the unique nature of the major.…”
Section: Sociodemographic Characteristics Of Participantssupporting
confidence: 76%
“…Table 2 shows the depression rate of medical and pharmacy students in a number of Vietnamese studies, showing that the depression rate of students is increasing, and this rate is quite consistent with quantitative studies, previously, most domestic and foreign studies showed that the rate of students suffering from depression was very high during their school years [12][13][14]. This is explained by the large amount of knowledge, dense class schedule as well as the unique nature of the major.…”
Section: Sociodemographic Characteristics Of Participantssupporting
confidence: 76%
“…: 228–230 (Lit. m.p: 228–232°C) [ 38 ] ; IR (KBr): ʋ = 3415, 3330, 2190, 1654, 1585 cm −1 ; 1 H NMR (400 MHz, DMSO‐d 6 ): δ (ppm) 9.63 (s, 1H, OH), 7.67 (s, 1H), 6.94 (s, 2H), 6.76 (s, 2H, NH 2 ), 6.63 (s, 2H), 6.44 (s, H), 6.36 (s, H), 4.46 (s, H), 3.03 (s, 3H), 2.82 (s, 3H).…”
Section: Methodsmentioning
confidence: 99%
“…: 190–193°C (Lit. m.p: 190–191°C) [ 38 ] ; IR (KBr) ʋ = 3440, 3330, 3021, 2192, 1530, 1350, 741 cm −1 ; 1 H NMR (400 MHz, DMSO‐d 6 ): δ (ppm) = 9.8 (s, 1H, OH), 8.09 (d, H, J = 4.0 Hz), 8.01 (s, 1H), 7.64 (t, 2H, J = 8.0 Hz), 7.04 (s, 2H, NH 2 ), 6.82 (s, H), 6.47 (d, 2H, J = 4.0 Hz), 6.43 (s, H), 4.9 (s, H).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, polysaccharides derived from C. sinensis have demonstrated significant antitumor, antioxidant, and immunomodulatory effects (7). Similarly, the extracted mycelial polysaccharides from O. sinensis have been found to possess strong antioxidant properties and offer health benefits in protecting against oxidative damage (8). Additionally, b-D-glucan, an exopolysaccharide from cultured mycelia of C. sinensis, exhibits strong antioxidant activity (9).…”
Section: Introductionmentioning
confidence: 99%